UNDERSTANDING THE CONCEPT OF EXORCISM: AN ANALYSIS OF THE HORROR FILM KUASA GELAP (2024) - Rudy, Rudy (IdeBahasa, 2025)
The practice of exorcism, which is often popularly used as a theme in horror films, is interesting and essential to study so that the concept can be understood properly. This study is expected to be useful as an additional reference for research purposes in the field of humanities and to increase knowledge about the concept of exorcism from different perspectives. The discussion focuses on constructing the meaning of exorcism through the Indonesian horror film Kuasa Gelap (2024). Scenes, plots, and dialogs gathered from the film are used as primary data to be analyzed and discussed. This study, which is categorized as library research, utilizes Stuart Hall's representation theory in analyzing and interpreting the representation of exorcism in the film. The meaning of exorcism is generally discussed from a religious perspective and the exploration of its meaning in this study is related to human life, not the supernatural or magical powers. The results of the data analysis reveal that the concept of exorcism in the film represents the unwillingness to accept the loss of a family member, strong determination for good intentions, and sincerity in praying.